Pengembangan Kuesioner Penilaian Proses Belajar Problem-Based Learning dengan Model SPICES - Surya Akbar; Mora Claramita; Tri Nur Kristina (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2014)
Background: Every medical education institution in Indonesia must used SPICES model as a strategy/approach on their curriculum. This accord with what is state in Standar Pendidikan Profesi Dokter Indonesia (SPPDI). Assessment of implementation of SPICES model in educational curriculum is highly important in determining the direction of learning process underway. The aim of this study is to develop a questionnaire that helps medical educational institution to assess degree of implement of SPICES model on their curriculum.Method: Questionnaire of Problem-based learning (PBL) learning process with SPICES model development made the two stages. First stage purpose was to develop questionnaire, while second stage was to validate of the questionnaire construct. First stage consists of three steps, i.e literature study, arrangements the items, and content validity. Construct validity of the questionnaire is done by used reliability test, and factor analysis test.Results: Result from questionnaire development in the first stage was 29 items. Construct validity process in the stage two produced 17 items.Conclusion: Assessment of PBL learning process with SPICES model questionnaire proven to be valid and reliable. Further investigation needs to assess stability of the questionnaire in other region.